HUBUNGAN MODAL SOSIAL PENYULUH PERTANIAN DENGAN KAPASITAS PETANI DALAM BERUSAHTANI SAYURAN DI KECAMATAN WUA-WUA KOTA KENDARI - Rivaldi Wardana Riman; Hartina Batoa; Ima Astuty Wunawarsih (Universitas Halu Oleo, 2022)
This research is motivated by weakened social capital which has an impact on farmer capacity due to the pandemic which has caused a lack of relations between extension agents and farmers. This research aims to determine the social capital of extension workers and to determine the capacity of vegetable farmers. The location determination was deliberately made because this sub-district has areas with various vegetable commodities and there are quite active agricultural extension workers. The population in this study were 219 farmers and a sample of 14% so that the sample in this study was 31 respondents. This type of research is descriptive quantitative. Data analysis used class intervals and routine scales (value scales). The results showed that the extensionist's social capital, namely trust, norms and networks, was in the high category and the farmer's capacity in vegetable farming as indicated by knowledge, attitudes and skills was in the high category. Keywords: Social Capital, Farmer Capacity, Vegetable Farming